Fertility Is Low When There Is No Societal Agreement on a Specific Gender Role Model - Ansgar Hudde (University of Bamberg, 2016)
Many authors argue that societal fertility levels are a function of changing gender relations, but the mechanism behind this association remains unclear and mainly untested. This paper argues that the variation in realized gender roles and gender role attitudes influences fertility: a great variation in attitudes among potential partners causes uncertainty and conflicts, which decreases people's propensity to choose to have a first or an additional child. How this idea is tested: macro-level regressions are run on 24 countries. A measure for the average gender role attitude as well as the dispersion in attitudes are regressed on the level of fertility. Attitudes are computed through factor analysis and capture opinions towards the gendered division of given tasks and privileges, such as childrearing or the uptake of parental leave. The measure includes attitudes towards different female and male roles. The dispersion in attitudes is the standard deviation of the factor variable in the given country. Attitudinal information are from the ISSP 2012. The analysis gives support to the hypothesis: the greater the variation in gender role attitudes, the lower is the fertility. The association is considerably strong, significant, and holds against various robustness checks.
Keywords: 330; fertility; gender role attitudes; gender revolution; cross-country comparison; CFR